Análise de tendência nas séries de precipitação na Região Metropolitana do Cariri – Ceará - Araújo, Hudson Mendes de (2020)
The evidence of climate change and its impact on the world is a constant problem that demands specific knowledge about its origin in order to minimize environmental disasters. Because these are cyclical events, it is possible to predict the occurrence of extreme events, such as floods and droughts. On the other hand, anthropogenic actions directly aggravate climate change. In view of this, this study consists of analyzing the trends of precipitation series in the Cariri Metropolitan Region using the Linear Regression and Mann-Kendall tests, using 30-year. With the application of the mentioned methodology, both tests used for each one of the nine cities studied presented the same angular coefficients, so it is possible to conclude that the Metropolitan Region of Cariri follows the annual trends obtained. It was also verified and confirmed that there is correlation between cities, pointing out that they have the same hydrological behavior. Finally, the need for water availability is confirmed, and this is possible due to both climatic changes and their rational use. Improper use directly impacts water quality and water cycles.